Adherence to behavioral targets and treatment attendance during a pediatric weight control trial12. (27th March 2013) - Theim, Kelly R.; Sinton, Meghan M.; Goldschmidt, Andrea B.; Van Buren, Dorothy J.; Doyle, Angela C.; Saelens, Brian E.; Stein, Richard I.; Epstein, Leonard H.; Wilfley, Denise E.
Abstract: Objective: Better weight loss outcomes are achieved in adults and youth who adhere to obesity treatment regimens (i.e., session attendance and prescribed changes in weight control behaviors). However, more research is needed regarding children's adherence to a range of behaviors relevant for weight maintenance over long‐term follow‐up. Design and Methods: Overweight children ( N = 101, aged 7‐12 years), along with an overweight parent, participated in a 20‐week family‐based behavioral weight loss treatment (FBT) and were then assigned to either a behaviorally focused or socially focused 16‐week weight maintenance treatment (MT). Treatment attendance and child and parent adherence (i.e., reported use of skills targeted within treatment) were examined in relation to child percent overweight change from baseline to post‐FBT, post‐MT, and 2‐year follow‐up. Results: Higher attendance predicted better child weight outcomes at post‐MT, but not at 2‐year follow‐up. Adherence to self‐regulatory skills/goal‐setting skills predicted child weight outcomes at 2‐year follow‐up among the behaviorally focused MT group. Conclusions: Future research is needed to examine mediators of change within family‐based weight control interventions, including behavioral and socially based targets. Incorporating self‐regulatory weight maintenance skills into a comprehensive MT may maximize children's sustained weight control.